2019
DOI: 10.3390/f10070598
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ecosystem Water Use Efficiency to Drought over China during 1982–2015: Spatiotemporal Variability and Resilience

Abstract: Ecosystem water use efficiency (WUE describes carbon-water flux coupling in terrestrial ecosystems. Understanding response and resilience of WUE to drought are essential for sustainable water resource and ecosystem management under increasing drought risks over China due to climate warming. Here we analyzed the response of ecosystem WUE to drought (spatiotemporal variability and resilience) over China during 1982–2015 based on an evapotranspiration (ET) dataset based on the model tree ensemble (MTE) algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 67 publications
9
30
0
1
Order By: Relevance
“…After severe drought, an ecosystem needs a recovery period [71]. If another drought occurs, the recovered ecosystem can respond quickly and to some extent ensure the stability of the ecosystem WUE level [9]. The resilience of ecosystem WUE found in this study is consistent with previous studies [26,69].…”
Section: Discussionsupporting
confidence: 89%
“…After severe drought, an ecosystem needs a recovery period [71]. If another drought occurs, the recovered ecosystem can respond quickly and to some extent ensure the stability of the ecosystem WUE level [9]. The resilience of ecosystem WUE found in this study is consistent with previous studies [26,69].…”
Section: Discussionsupporting
confidence: 89%
“…Their value is larger than our simulated value because they used GPP instead of NPP. In previous studies, forests and grasslands were demonstrated to have the highest and lowest WUE values (Guo et al, 2019; Liu et al, 2015; Zhu et al, 2015), respectively. WUE results obtained via our simulation were found to exhibit a similar trend, with the highest values being associated with forests, followed by shrublands, and grasslands.…”
Section: Discussionmentioning
confidence: 91%
“…The annual WUE value for the TP during the period of 1979–2010 was calculated to be approximately 0.38 g C kg −1 H 2 O in our study; this value is in good agreement with their results. Guo et al (2019) showed that TP had a lowest WUE of 0.78 g C kg −1 H 2 O compared with other subregions in China. Their value is larger than our simulated value because they used GPP instead of NPP.…”
Section: Discussionmentioning
confidence: 99%
“…Drought could induce stomatal closure to reduce water loss, thus decreasing carbon uptake. The response of WUE varies among ecosystems [ 22 , 23 ] and droughts with different duration and severity [ 24 , 25 ]. Higher WUE during droughts was found in Northeast China and South China comprised of abundant forests, whereas WUE was decreased over northwestern China [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The response of WUE varies among ecosystems [ 22 , 23 ] and droughts with different duration and severity [ 24 , 25 ]. Higher WUE during droughts was found in Northeast China and South China comprised of abundant forests, whereas WUE was decreased over northwestern China [ 23 ]. However, how the multiple ecosystem metrics (GPP, NPP, LAI, and WUE) respond to flash droughts and how the response time varies over different regions remain unclear.…”
Section: Introductionmentioning
confidence: 99%